2022
DOI: 10.1021/acs.jmedchem.2c00604
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent and Selective Receptor-Interacting Serine/Threonine Protein Kinase 2 (RIPK2) Inhibitors for the Treatment of Inflammatory Bowel Diseases (IBDs)

Abstract: Receptor-interacting serine/threonine protein kinase 2 (RIPK2) has been demonstrated to be a promising target for treating inflammatory diseases. Herein, we describe the discovery and optimization of a series of RIPK2 inhibitors derived from an FLT3 inhibitor, CHMFL-FLT3-165. Compound 10w was identified to possess an IC50 value of 0.6 nM for RIPK2 and greater than 50,000-fold selectivity over its family homologous kinase RIPK1 (IC50 > 30 μM). It exhibited high kinase selectivity and inhibited RIPK2 to prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In our previous studies on the screening of RIPK2 inhibitors, we occasionally found that compound L1 could induce potent and rapid vacuolization in the rat cardiomyocyte cell line H9C2 when RIPK2 inhibitors were evaluated for cell toxicity in our recent research. 26 Moreover, compound L1 could completely induce vacuolization phenotype in human cervical adenocarcinoma cell line HeLa and human triple-negative breast cancer cell line MDA-MB-231 cells at 1 μM. This unexpected finding has aroused our great interest to explore the mechanism and further structural modifications based on L1, with MOMIPP, D-13, and apilimod as positive 1.…”
Section: ■ Biological Results and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In our previous studies on the screening of RIPK2 inhibitors, we occasionally found that compound L1 could induce potent and rapid vacuolization in the rat cardiomyocyte cell line H9C2 when RIPK2 inhibitors were evaluated for cell toxicity in our recent research. 26 Moreover, compound L1 could completely induce vacuolization phenotype in human cervical adenocarcinoma cell line HeLa and human triple-negative breast cancer cell line MDA-MB-231 cells at 1 μM. This unexpected finding has aroused our great interest to explore the mechanism and further structural modifications based on L1, with MOMIPP, D-13, and apilimod as positive 1.…”
Section: ■ Biological Results and Discussionmentioning
confidence: 97%
“…The synthesis route of intermediate 1 has been reported previously. 26 The corresponding compounds L1 and L6−23…”
Section: ■ Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Yuan et al designed a new series of RIPK2 pyrrolopyrimidine inhibitors based on structural modification of the FLT3 inhibitor CHMFL-FLT3-165 ( Figure 12 ) ( Wu et al, 2016 ; Yuan et al, 2022 ). CHMFL-FLT3-165 strongly inhibited RIPK2 and RIPK5 at 1 μM concentration.…”
Section: Ripk2 Inhibitorsmentioning
confidence: 99%
“…These compounds were used as the chemical probes to investigate the RIPK2 kinase and NOD signalling functions. Although these compounds bear potent inhibition and good selectivity, moderate PK properties limited their further development to enter into clinical study, and more research was going on 17–21 . Notably, GSK2983559 22 , a prodrug of compound P5 23 , has good kinase specificity and excellent activity in vivo.…”
Section: Introductionmentioning
confidence: 99%